1998
DOI: 10.1038/sj.cdd.4400354
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic oncogenes prevent caspase-dependent and independent commitment for cell death

Abstract: Apoptosis is a morphologically defined type of cell death associated with the activation of certain proteases belonging to the ICE/CED-3 family, known as caspases. Resistance to apoptosis has been implicated as one of the mechanisms that participates in oncogenesis. We found that the broadspectrum peptide inhibitor of the caspases, zVAD-fmk, interferes in a dose-dependent way with all the morphological and biochemical changes associated with apoptosis induced by anti-CD95 mAb, staurosporine, VP-16 and Act-D. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
5

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 32 publications
10
100
1
5
Order By: Relevance
“…Thus, pretreatment of Jurkat cells with zVADfmk inhibited anti-CD95 mAb triggered apoptosis, but not drug-induced apoptosis, with actual cell survival and maintenance of clonogenic potential, suggesting caspasedependent or caspase-independent commitment to cell death, according to circumstances. 40 This could provide an explanation for the opposite results concerning the consequences of caspase inhibition. However, in the present study, zVAD-fmk partly protected thymocytes from spontaneous and from dexamethasone-induced apoptosis while it totally failed to prevent the commitment to cell death in similarly treated B cells.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, pretreatment of Jurkat cells with zVADfmk inhibited anti-CD95 mAb triggered apoptosis, but not drug-induced apoptosis, with actual cell survival and maintenance of clonogenic potential, suggesting caspasedependent or caspase-independent commitment to cell death, according to circumstances. 40 This could provide an explanation for the opposite results concerning the consequences of caspase inhibition. However, in the present study, zVAD-fmk partly protected thymocytes from spontaneous and from dexamethasone-induced apoptosis while it totally failed to prevent the commitment to cell death in similarly treated B cells.…”
Section: Discussionmentioning
confidence: 94%
“…This applies to a number of different models of apoptosis induced by overexpression of bax (55), c-myc overexpression, and serum withdrawal or overexpression of bak (56), protonophore, protoporphyrine IX, dexamethasone, ceramide, etoposide, or nitric oxide (57-62) and cytotoxic T lymphocyte granule exocytosis (63). However, Bcl-2 maintains survival of cells that have been induced to die in a caspase-independent manner with glucocorticoids, growth factor withdrawal, c-Myc, Bax, or Bak (55,56,61,62). Therefore, the down-regulation of Bcl-2 in calphostin C-induced apoptosis is an important commitment event that determines whether or not a cell dies even when it is independent of caspase activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classic apoptotic pathways, studies have demonstrated that cytochrome c-, Apaf-1-, or caspases-deficient cells can still undergo apoptosis (Kuida et al, 1996;Cecconi et al, 1998;Hakem et al, 1998;Yoshida et al, 1998;Li et al, 2000). In addition, apoptosis induced by some stimuli cannot be inhibited by the pan-caspase inhibitor z-VAD-fmk (Amarante-Mendes et al, 1998;Bidere and Senik, 2001). These studies suggest that caspase-independent apoptotic pathways exist.…”
Section: Introductionmentioning
confidence: 99%